Evaluation of Drought Stress Tolerance Based on Selection Indices in Haricot Bean Varieties Exposed to Stress at Different Growth Stages - Awoke Wasae (International Journal of Agronomy)
A pot experiment was conducted at Hawassa University, Ethiopia, with the objectives of identifying relatively drought-tolerant haricot bean varieties and identifying sensitive growth stages of this plant to drought stress based on selection indices under greenhouse conditions. Ten improved haricot bean varieties were subjected to drought stress at vegetative, flowering, and pod setting stages by withholding water for 15 days. Seed yields (g plant−1) under stress (Ysi) and nonstress (Ypi) conditions were recorded, and all indices were calculated for the three drought stress levels (vegetative, flowering, and pod setting) against the yield obtained from the nonstress (Ypi) treatment. Drought intensity indices at vegetative, flowering, and pod setting stages were 0.046, 0.335, and 0.249, respectively. Drought stress imposition at the flowering stage resulted in high values of DII, DSI, PYR, and SSPI and low values of DRI, GM, MP, YSI, MRP, REI, and RDI reflecting that flowering is the most sensitive growth stage to drought stress. Low values of DSI, PYR, and SSPI and high values of DRI, GM, MP, YSI, MRP, REI, and RDI for H/dumme, Wajo, and Nasir confirmed that they are tolerant to drought stresses that occur at different growth stages. Those varieties also showed the best mean of rank and low standard deviation. A strong association between Ypi and Ysi was observed under drought stress at the vegetative stage but not under flowering and pod setting stages. Ysi had a positive correlation with DRI, GM, MP, MRP, and REI while a significant and negative correlation with PYR and DSI depicting that they are a better predictor of potential yield under a stress condition and they can use as a morphological marker by the plant breeder.